Avaliação hidrossedimentológica de uma pequena bacia em urbanização - Costas, Marcel Felipe Tonetto (2003)
The objective of this research is to do a evalvulation of the Basin Alto da Colina, in urbanization process , situed in Santa Maria – RS. In this way, to made use of fluvimetric station installed in that basin and collect data sedimentometrics and hydrometrics. The data were collected with manual sampler (A M S – 1) and automatic sampler (ANA) and analised the concentration of sediments for the filtration method and granulemetry for the deep remove method. The sediments concentration in the beggining of the flood annual is to raise, presented a sharp, showing the washed streets charge. The suspention granulemetry of the material show a sand tenor of 47% beyond expected because the kind of the soil that form the basin denomined Podzólico Bruno Acinzentado Álico. The sediment’s concentration obtained with the manual sampler in flood events presented a nice correlation with the flow, allowed the rating curve building. The correlation between the roiliness and the sediments concentration presented a Nice correlation with the sampler A M S – 1 and roiliness machine mesure SL2K with a R2 equal 0,9260. In apite of Nice correlation, when try stabilish a Rating curve of concentration, the same can´t de used, because existed a great discrepancy between the calculated concentration in this way and the concentration mesure in the station hydrological observing. For the determination of the sediments production transported in suspension to made use of Modified Universal Soil Lost Equation, MUSLE, propose for Williams (1975) the showed higher valves calculated wih the Rating curve of concentration in function of the shar and the first flush.